Test treatment of advanced breast cancer with dichloro diphenyl dichloroethane - Cáceres C., Eduardo (2015)
Five cases with advanced carcinoma of the breast have been treated with op'DDD. In all instances the urinary excretion of 17 KS and 17 OH was diminished but not abolished. The toxic effects were nauseas, vomiting, diarrhea, headache, dizziness and weakness. From the present study it is not posible to conclude on the effeet of the drug upon the hepatic function. In three of the five cases, progression of the disease was observerd, in one case the lesion remained stacionary during the treatment and in the other one an objective improvement was obtained.